2001
DOI: 10.1051/jp4:2001833
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic transformations of Cu-Al-Ni single crystals in tension/compression

Abstract: Abstract. Cu-AI-Ni alloys, similarly as other Cu-base shape memory alloys, transform into more martensitic structures c^' (6R), Pi' (18R) and y x ' (2H), depending on the temperature, stress, load axis orientation, sense of loading and composition. The transformation stress-temperature conditions at which individual transitions take place are beneficially represented in so called non-equilibrium stress-temperature phase diagrams. On the basis of the Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Let us compare briefly the transformation behavior of strained thin foils with the transformation responses of bulk single crystals, expressed conventionally in the form of -T phase diagrams [2,[4][5][6]. We shall compare our observations with the results by Otsuka et al [2] who tensile strained CuAlNi single crystals of a composition and orientation very similar to our foils.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Let us compare briefly the transformation behavior of strained thin foils with the transformation responses of bulk single crystals, expressed conventionally in the form of -T phase diagrams [2,[4][5][6]. We shall compare our observations with the results by Otsuka et al [2] who tensile strained CuAlNi single crystals of a composition and orientation very similar to our foils.…”
Section: Discussionmentioning
confidence: 68%
“…In the presence of an external stress, multistage thermoelastic behavior is observed reflecting variety of successive austenite-to-martensite and martensite-to-martensite transitions [2][3][4][5][6]. Beside 1 and 1 martensites, also 1 structure was reported in CuAlNi single crystals subjected to tensile stress in the [100] 1 direction [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar history dependent phenomena are frequently encountered in SMA single crystal experiments. Recently, they have been observed on CuAlNi [16,19]. When the crystals were deformed in compression in the low temperature state and unloaded, the reverse transformation temperature shifted significantly upwards.…”
Section: Stress [Mpa]mentioning
confidence: 93%
“…These experiments were limited to tension, except for a paper [9] where cyclic tests were performed, yet at temperatures only above A f . Our previous studies on other Cu-base SMA have clearly demonstrated a strong dependence of their thermoelastic behaviour on the sense of loading (tension-compression) and transformation history [12][13][14][15][16]. The knowledge of these effects was employed in modelling SMA polycrystals [17,18].…”
Section: Introductionmentioning
confidence: 98%